Hubungan Persepsi Konsumen Terkait Kualitas, Harga dan Hygiene Sanitasi terhadap Keputusan Pembelian Makanan di Kawasan Kambang Iwak - Rafif Bagaskara; Dini Arista Putri; Imelda Gernauli Purba; Ery Erman (Jurnal Kesehatan Komunitas, 2026)
Consumer perception plays an important role in determining food purchasing decisions, especially in assessing the quality, price, and hygiene aspects of food sanitation. These factors can affect the level of consumer trust and interest in choosing and consuming food in a place. The purpose of this study was to analyze the relationship between consumer perceptions regarding quality, price, and food hygiene sanitation to food purchasing decisions in the Kambang Iwak area of ​​Palembang City. This study aims to analyze the relationship between consumer perceptions regarding quality, price, and food hygiene sanitation with food purchasing decisions in the Kambang Iwak area of ​​Palembang City. This study used an analytical method with a cross-sectional design and involved 95 respondents selected through a purposive sampling technique. Data collection was carried out through interviews using questionnaires, while data analysis included univariate and bivariate analysis with the Spearman Rank correlation test using a statistical program. The results showed a significant relationship between quality (p = 0.025), price (p = 0.001), and perceptions of food hygiene sanitation (p = 0.000) to food purchasing decisions. The conclusion of this study reveals that there is a very strong correlation (ρ=-0.780) but in the opposite direction between the perception of food hygiene sanitation and food purchasing decisions. In other words, the more positive the consumer's perception of food hygiene and sanitation, the lower their tendency to make repeat purchases, even potentially not buying again. The suggestion of this study is that consumers should pay more attention to the aspects of food hygiene and sanitation before making a purchase.